Redefining and Regulating the New Sharing Economy - Scott,Inara; Brown,Elizabeth (University of Pennsylvania Journal of Business Law, 2017)
While proponents of regulating the sharing economy suggest a need to protect public health, workers, and incumbent businesses, to ensure localities are made whole for the use of public services, opponents of regulation argue that government intervention will stifle innovation and undermine economic and community benefits. The problem with both sides of this argument is that advocates and detractors alike often fail to address the wide differences among the practices and business entities that currently fall under the same umbrella. To address this inappropriate conflation and the resulting confusion among consumers and regulators alike, the goal of this article is to define the sharing economy as it now stands and to create a taxonomy that distinguishes and differentiates the various types of business entities that have been lumped into it. This article then proposes regulatory responses to the differing categories in the taxonomy based on the risks they present.
Keywords: Business Law